Pengaruh Penggunaan Media Photovoice Terhadap Keterampilan Menulis Siswa Kelas 3 Sekolah Dasar - Ajeng Nurmadi Cahyanti; Ermawati Zulikhatin Nuroh (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2023)
Students' difficulties in using good and correct Indonesian became the inspiration for this research. This can be seen from the use of incorrect words, weak phrases, and typos when writing simple narrative essays. The purpose of this research is to find out how the use of photovoice media has an impact on the writing ability of third grade elementary school children. One Group Pretest-Posttest Design was used in conducting this research as an experimental research approach. Twenty third grade students at SDN Krembung 1 were included in the research sample which was taken through saturated sampling. Writing skills assessment (before and after the test) and activity documentation were used as the data collection approach, together with observation as the main source of information. The data were examined using the normality test, and a Paired Sample T-Test was performed because the data were found to be regularly distributed. The findings of the Paired Sample T-Test show that Sig. (2-Tailed) is 0.000 < 0.05. It can be determined that the use of photovoice media has a major impact on the writing skills of grade 3 students at SDN Krembung 1.